Individual Intentions to Engage in Earnings Management: Investigating the Role of Behavior, Machiavellianism, and Ethical Climate - Sayal, Kangan (My University, 2022)
The recent spate of accounting scandals and the collapse of high-profile organizations have raised concerns regarding Earnings Management (EM) practices by accounting professionals and have brought considerable disrepute to organizations and societies. EM involves intentional manipulation of accounting numbers in the financial reporting by individuals to mislead some stakeholders or to achieve a strategic purpose. Despite strict regulatory reforms intending to restrain aggressive financial reporting, EM continues to persist and has become a matter of concern for standard setters, regulators, and practitioners. EM as a phenomenon is complex that does not solely depend on external pressures and internal incentives; rather it is more of an individual act involving a complex mix of personal and organizational contextual factors. However, a limited focus on individuals as a central element behind EM has restricted the ability to understand what drives the individual to cross ethical boundaries and indulge in EM. This research focuses on the individual perspective in EM and investigates the role of personal psychological factors and organizational Ethical Climate (EC) in influencing individuals’ intentions to engage in EM. Through an extant review of literature, a set of personal psychological factors have been identified within the theoretical lens of the Theory of Planned Behavior (TPB) (Ajzen, 1991) and the dark triad of personality theory (Christie and Geis, 1970). Further, through the theoretical lens of EC theory (Victor and Cullen, 1987), the model identifies the EC types as a likely moderator influencing individuals’ intentions to engage EM. After identifying the factors, possible relationships have been established between the variables, and a comprehensive EM behavior model has been proposed along with the corresponding hypotheses. Further, the questionnaire was developed using the existing scales from the literature. The sampling technique used was a combination of snowball and convenience sampling. The prospective respondents were the chief financial officers and senior accounting managers of both public and private organizations across India. The data collected was subject to Confirmatory Factor Analysis (CFA) to create the measurement model and establish goodness-of-fit. The CFA results confirmed that the adjusted measurement model met all the requirements of composite reliability, convergent validity, and discriminant validity. After that, structural equation modeling was run on the measurement model to test direct and moderating hypotheses, and mixed results were found. The research findings revealed a significant influence of personal psychological factors on individuals’ intentions to engage in EM. It showed that individuals’ Attitude Towards Behavior (ATB), Perceived Behavior Control (PBC), Moral Obligation (MO), and Machiavellianism personality trait significantly influence individuals’ intentions to engage in EM. These findings indicate that individuals who consider their own beliefs or their own evaluation of engaging in EM as important (ATB), who possesses the ability to manipulate and make use of available opportunities and resources to engage in EM (PBC), does what feels right based on their personal responsibility and not on the opinion of others (MO), and possesses deceitful and manipulative behavior (Machiavellianism personality) are more likely to show intentions to engage in EM. Contrary to previous research, the empirical findings reveal that Subjective Norms (SN) did not significantly influence individuals’ intentions to engage in EM, implying that the opinion or approval of significant others holds little importance when deciding to perform EM. This could be probably because the respondents in this research, being the chief financial officers and senior accounting managers, hold a higher level of education, have greater work experience, have more power and control, and are less likely to worry about their actions being subject to any kind of reward or punishment by referent others. This makes the influence of the opinion of significant others (SN) on the decision to engage in EM seem insignificant and weak. Further, regarding the moderating influence of EC types on individuals’ intentions to engage in EM, the findings revealed a weak moderating influence of egoistic climate. This is because the individuals in this research did not perceive their organizational climates as highly egoistic. The finding signifies that in the presence of a low level of egoistic climate, individuals are less like to form intentions to engage in EM, even if they have positive attitude towards EM (ATB), possesses required opportunities and resources (PBC), and do what feels right based on their sense of responsibility (MO). That is, a low level of egoistic climate neutralises the influence of these personal psychological factors on individuals’ intentions to engage in EM to some extent. The findings also revealed that a benevolent climate significantly moderates individuals’ intentions to engage in EM. The moderating influence of a benevolent climate, therefore, suggests that despite individuals believing that engaging in EM is not highly unethical, they are less likely to form behavioral intentions to engage in EM when they perceive their organizational climate to be characterized by a concern for social responsibility and emphasizing on serving the public interest. Lastly, the principle climate, which focuses on following a professional code of ethics, rules, and laws for the good of others, also appeared to have the expected moderating influence on individuals’ intentions to engage in EM. This implies that in the presence of an organizational climate emphasizing more on following rules, laws, and professional codes of ethics, the influence of personal psychological factors on individuals’ intentions to engage in EM was not as strong as it was otherwise. Thus, the principle climates appeared to have weakened individuals’ intentions to engage in EM. This makes the perceived EC of organizations a key organizational factor that indirectly influences individuals’ intentions about issues with ethical content, like EM. This research makes an important contribution to EM literature by developing a theory-informed EM behavior model that documents the role of personal psychological factors and organizational EC in influencing individuals’ intentions to engage in EM, thereby fulfilling the objectives of the research. These insights would enable organizations and policymakers to develop policies and training programs to prevent the misreporting of financial information. They would also help educators to train students, thereby positively shaping students’ ethical behavior. Therefore, the research findings emphasize that to maintain the credibility of financial information and the integrity of the accounting profession, policymakers, regulators, and organizations must consider the previously ignored central element behind accounting frauds involving EM, that is, individuals.
Keywords: Earnings Management; Theory of Planned Behavior; Machiavellianism; Ethical Climate; Earnings Management Intentions